Towards the Absolute Zero - WEINTROUB, S. (Nature, 1952)
Low Temperature Physics Four Lectures. By F. E. Simon, N. Kurti, J. F. Allen, K. Mendelssohn. Pp. vi + 132. (London: Pergamon Press, Ltd., 1952.) 21s.